Analysis and identification of flavonoid compounds in kepok banana corm extract (musa paradisiaca L) - Andini, Andini; Sari, Meiria Istiana; Raharjo, Sentot Joko; Anneke, Anneke (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2024)
Kepok banana corm is one of the natural ingredients that has been obtained and can provide many benefits because of its excessive flavonoid content. This study aims to determine the types of flavonoids contained in the kepok banana weevil extract. Methods of detection and discovery of flavonoid measurement methods used include reaction, thin layer chromatography, and LC-MS/MS, and spectrofotometri for total flavonoid content compared to rutin as a flavonoid standard. The results showed that kepok banana corm extract contains a class of flavonoid compounds including rutin, kaempferol 3-O-rhamnoside-7-O-glucoside, quercetin 3 glycocide, and chrysoeriol-7-O-glycuronyl, with a total flavonoid content of 6.19. ±0.65%.